A INFLUÊNCIA DOS PROVENTOS E DA RESTRIÇÃO FINANCEIRA NA INFORMATIVIDADE DOS LUCROS: EVIDÊNCIAS NO MERCADO BRASILEIRO - Souza, Ana Carolina dos Santos (2019)
This study investigates the influence of the cash distribution on the informativeness of earnings considering the effect of financial constraints on the Brazilian shares of firms listed in B3. The sample consisted of 223 companies from 2011 to 2018, total